My Diabetes Apps: improving knowledge, compliance, and control in uncontrolled type 2 diabetes patients in Kedah, Malaysia - Jamhari, Mohd Nazrin; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Hassan, Mohd Rohaizat; Ahmad, Norfazilah; Sharif, Khaironi Yatim; Muhammad, Muhammad Sufri; Osman, Mohd Hafeez; Zakaria, Muhammad Luqman; Shahabudin, Winda Zulaiha; Wan Ibadullah, Wan Abdul Hannan; Chi Habudin, Ainul Mardhiyah; Mohd Ghazali, Qistina (Education in Action, 2024)
Usage of mobile applications can be the game changer in managing diabetes patients and reducing the percentage of uncontrolled diabetes cases in Malaysia. This study aimed to measure the effectiveness of the locally developed diabetes mobile applications in improving knowledge, compliance and control of Type 2 Diabetes Mellitus patients. Methods: In the first phase, content of the mobile application was developed using Nominal Group Technique discussion by 11 experts. The produced prototype, My Diabetes Apps© undergone the second phase of pilot study for validation, SKAMA evaluation form. Final third phase interventional study was conducted in two districts in the state of Kedah (Kuala Muda as the control group, Kota Setar as the intervention group), involving eight health clinics. 82 respondents were selected using multi-stage random sampling technique among uncontrolled Diabetes Mellitus patients over four months. Results: Thirteen key contents recommended by the expert panels as mandatorily important for diabetic patients. The mean(±sd) usability score of My Diabetes Apps was 86 (±10.90), indicating the usability of the mobile application. The intervention study found there was significant difference in the mean knowledge score between the control group and the intervention group [F(1.79)=42.27; p<0.001] and mean HbA1C between groups pre and post intervention [F(1.79)= 6.03; p=0.016]. No difference in the mean value of the compliance score between the two groups [F(1.79)=1.58; p=0.212]. Conclusion: My Diabetes Apps© proved to be improve patient knowledge and helpful in diabetic control. Integrating the technology in patient’s care improves patients’ self-efficacy and monitoring of diabetes.